Sawasiray and Pitusiray: Sacred landscape, ancestors, water and fertility - Ortiz Luna, Alejandro J. (2022)
The present work is a deep and interdisciplinary look at the portions of the landscape considered sacred in ancient times, particularly in the Cusco region. The identification of rock formations linked to the Apu Sawasiray-Pitusiray (Calca, Cusco), related archaeological remains, the rescue of ancestral memory addressing concepts of ancestors, water and fertility of the land, allowed us to understand the symbolic conception of the landscape nature and its relationship with the built environment. This research case considers that the study of archaeological landscapes in the pre-Hispanic Andes requires, on the one hand, a contextualization outside Western canons and, on the other, the use of an ontological corpus that allows the analysis of concepts and own perceptions of the society studied.